In vitro diagnostic methods of Chagas disease in the clinical laboratory: a scoping review - Ascanio, Luis C.; Carroll, Savannah; Paniz-Mondolfi, Alberto; Ramírez, Juan David (Frontiers in Microbiology, 2024)
Background: Chagas disease (CD), caused by Trypanosoma cruzi, is a global health concern with expanding geographical reach. Despite improved and accessible test methods, diagnosing CD in its various phases remains complex. The existence of clinical scenarios, including immunosuppressed patients, transplant-related CD reactivation, transfusion-associated cases, and orally transmitted acute infections, adds to the diagnostic challenge. No singular gold standard test exists for all phases, and recommendations from PAHO and the CDC advocate for the use of two serological methods for chronic CD diagnosis, while molecular methods or direct parasite detection are suggested for the acute phase. Given the complexity in the diagnostic landscape of CD, the goal of this scoping review is to characterize available diagnostic tests for CD in the clinical laboratory.Methods: A literature search in PubMed was conducted, with inclusion criteria focusing on studies related to In-Vitro diagnosis (IVD) in humans usingpublished in English, Spanish, or Portuguese language. as of August 28, 2023, and extended backward with no predefined time frame.Studies underwent title and abstract screening, followed by full-text review. Studies included were classified based on the diagnostic method used. Test methods were grouped as serological, molecular, and other methods. Performance, availability, and regulatory status were also characterized.: Out of 85 studies included in the final review, 115 different tests were identified. These tests comprised 89 serological test types, 21 molecular test types, and 5 other test methods. Predominant serological tests included ELISA (38 studies, 44.70%), Rapid tests (19 studies, 22.35%), and